PENGEMBANGAN SOAL TES BERPIKIR KRITIS PADA PEMBELAJARAN MATEMATIKA SISWA KELAS 1 SEKOLAH DASAR - Ariani, Rini; Mhmd Habibi (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This study intends to develop a critical thinking question grid instrument in grade I mathematics learning. This study aims to measure the instrument of critical thinking questions that are valid, reliable and the level of difficulty. The critical thinking indicators used in this study are interpretation, analyzing and evaluating. This research uses the Research and Development (R & D) research method or research and development with the 4D development model which is simplified to 3D. In this study involved 15 respondents of class I students of SDN 032 kualu, as for the form of instrument lattice questions developed in the form of essay questions totaling 15 items. The results of the research analyzed using SPPS version 25.00 for windows show that all questions are valid with a significant level of r table value for df (N-2) at a significant level of 0.05 is 0.5140, that is, if r count> from r table then the question is said to be valid. For the reliability of the question, the Cronbach alpha result is 0.882, if sig. more than 0.60, it is declared reliable and can be used. For the level of difficulty of the 15 questions, there are 7 questions in the easy category, namely question numbers 1, 2, 3, 4, 9, 11 and 14. For questions in the medium category, there are 6 items, namely question numbers 5, 6, 7, 8, 10 and 15. In addition, there are 2 items in the difficult category (SR), namely question numbers 12 and 13. So it can be concluded that the question grids developed can be used to improve students' critical thinking skills